2020
DOI: 10.1051/e3sconf/202015101028
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Anopheles balabacensis as natural vector of malaria caused by Plasmodium knowlesi inhabits forested areas in Kecamatan Balik Bukit, Western Lampung Regency

Abstract: This study was conducted to confirm the Anopheles spp as malaria vector inhabits forested areas in Western Lampung Regency, Sumatra Island, Indonesia. Anopheles spp. were sampled using the human landing catch method at a remote forest habitat. Each caput and thorax of Anopheles balabacensis specimen was placed separately inside a sterilized mortar and the tissue homogenized using a sterile pestle. The total DNA was extracted from the tissues according to QIAamp DNA Mini Kit protocol. The presence of malaria pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Anopheles leucosphyrus is located in all provinces of Sumatra and in all provinces of Kalimantan except Central Kalimantan [ 34 , 36 ]. Anopheles balabacensis is present in North, South, and East Kalimantan, Sumatra (Aceh, Jambi, Bengkulu, Lampung), Riau islands, Java (Central and Yogyakarta), West Nusa Tenggara, and North Sulawesi [ 34 37 ], whereas An. introlatus is only found in the provinces of Sumatra [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anopheles leucosphyrus is located in all provinces of Sumatra and in all provinces of Kalimantan except Central Kalimantan [ 34 , 36 ]. Anopheles balabacensis is present in North, South, and East Kalimantan, Sumatra (Aceh, Jambi, Bengkulu, Lampung), Riau islands, Java (Central and Yogyakarta), West Nusa Tenggara, and North Sulawesi [ 34 37 ], whereas An. introlatus is only found in the provinces of Sumatra [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, P. knowlesi DNA was detected in an An. balabacensis from Lampung province [ 37 ]. Data on P. knowlesi vectors and hosts were extracted from the studies listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Given this requirement, continued surveillance and mitigation of P. knowlesi throughout at-risk regions of Indonesia will be important. Between the period of 2015 and 2020, a small number of studies have identified substantial numbers of P. knowlesi infections within Indonesia [68][69][70], particularly within northern Sumatra [56,71,72], a region identified as a valuable target for surveillance effort in the 2015 model [31]. Despite this, the Indonesian region of Kalimantan on the island of Borneo still has a relative scarcity of occurrence data given its high predicted transmission suitability and the number of P. knowlesi cases reported in adjacent areas of Malaysia.…”
Section: Discussionmentioning
confidence: 99%